Why do universities have little systemic impact with social innovation? An institutional logics perspective - Cinar, Ridvan; Benneworth, Paul (Growth & Change, 2021)
Social innovation has been increasingly regarded as an instrument through which transformative structural change, necessary to address grand societal challenges can be achieved. Social innovations are encouraged by the emergence of innovation systems that support changes not exclusively driven by a techno-economic rationality. In the context of this special issue, there has been both little understanding of social innovation systems within mainstream innovation ecosystem approaches and little analysis of the roles played by universities in social innovation systems. We here focus on the institutional complexity of universities and their field-level dynamics as serving as a potential break on the institutionalisation of social innovation. To deepen our understanding of this, we utilise a literature around institutional logics to foreground characteristics of organisational fields with regard to social innovation. Drawing on empirical data gathered in two public universities located in different countries, we show that in one case the potential of social innovation is undermined by two dominant institutional logics, in the other its permeation across the organisational field is seriously challenged by a more powerful dominant logic. The institutional logic approach is useful to highlighting the barriers to building productive innovation ecosystems incorporating social considerations, and helps to explain the persistent difficulties in reframing ecosystems approaches to reflect wider societal dynamics.
Keywords: Réservé UdeM; Rôle des universités